PREVALENCE OF MULTIDRUG-RESISTANT ORGANISMS IN PEDIATRIC PATIENTS WITH LOWER RESPIRATORY TRACT INFECTIONS (Journal of Medical & Health Sciences Review, 2025)
Background: Lower respiratory tract infections (LRTIs) are a major cause of childhood morbidity and mortality, and their management is increasingly complicated by multidrug-resistant organisms (MDROs).Objective: To determine the prevalence, resistance patterns, and clinical associations of MDROs in pediatric patients with LRTIs.Methodology: This descriptive cross-sectional study was conducted in the Department of Pediatrics, AIMS Hospital, Muzaffarabad, in collaboration with the Department of Microbiology and the Department of Pharmacology, University of Balochistan, from January to December 2023. A total of 422 children aged 1 month to 15 years admitted with clinically and radiologically confirmed LRTIs were included. Respiratory specimens were processed for bacterial identification and antimicrobial susceptibility testing according to CLSI guidelines. Multidrug resistance was defined as resistance to at least one agent in three or more antibiotic classes. Data were analyzed using SPSS version 26.0, with chi-square and t-tests applied where appropriate.Results: Of the 422 patients, 246 (58.29%) were male and 176 (41.71%) were female, with the most common age group being 1–5 years (178, 42.18%). Pneumonia was the leading diagnosis (274, 64.93%), and 112 (26.54%) patients required ICU admission. Bacterial isolates were dominated by Klebsiella pneumoniae (128, 30.33%), Pseudomonas aeruginosa (92, 21.80%), and Escherichia coli (76, 18.01%). Overall, 196 (46.54%) isolates were identified as MDROs. ICU patients had a significantly higher prevalence of MDROs (57.14%) compared to ward patients (42.58%, p = 0.014). High resistance was observed against β-lactams, particularly in Acinetobacter baumannii (82.81%) and K. pneumoniae (78.13%).Conclusion: Nearly half of pediatric LRTIs were caused by MDROs, highlighting the urgent need for effective antimicrobial stewardship and infection control strategies.